2023
DOI: 10.1186/s12889-023-15350-2
|View full text |Cite
|
Sign up to set email alerts
|

Cigarettes smoking and e-cigarettes using among university students: a cross-section survey in Guangzhou, China, 2021

Abstract: Background There is an increase in the use of cigarettes and e-cigarettes worldwide, and the similar trends may be observed in young adults. Since 2014, e-cigarettes have become the most commonly used nicotine products among young adults (Sun et al., JAMA Netw Open 4:e2118788, 2021). With the increase in e-cigarette use and the decrease in use of cigarettes and other tobacco products, however, there is limited information about Chinese smokers, e-cigarettes users and trends in cigarettes and e-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
1
1
Order By: Relevance
“…These findings are consistent with previous studies; one conducted on medical students at National Ribat University, Khartoum, and another in Ethiopia, a neighbouring country 13 , 15 . However, the prevalence rate is significantly lower than those reported in China and Turkey 21 , 22 . The observed disparity in prevalence rates may be attributed to the higher smoking rates observed among Southeast Asians and Europeans compared to Africans 6 .…”
Section: Discussioncontrasting
confidence: 57%
“…These findings are consistent with previous studies; one conducted on medical students at National Ribat University, Khartoum, and another in Ethiopia, a neighbouring country 13 , 15 . However, the prevalence rate is significantly lower than those reported in China and Turkey 21 , 22 . The observed disparity in prevalence rates may be attributed to the higher smoking rates observed among Southeast Asians and Europeans compared to Africans 6 .…”
Section: Discussioncontrasting
confidence: 57%
“…O comportamento de fumar entre adolescentes é influenciado pela companhia de amigos fumantes, pela exposição a informações sobre CE e pela presença de familiares que também fumam 33 . Além disso, conexões sociais com outros usuários afetam a percepção de risco e a disposição para parar de fumar 34 . No ambiente universitário, fatores como gênero, educação, estilo de vida e emoções também moldam o uso de cigarros convencionais e eletrônicos, com a norma social, expectativas de resultados e motivações pessoais, sendo importantes para entender o uso de sistemas eletrônicos de administração de nicotina, ressaltando a necessidade de abordagens diversificadas para reduzir esse consumo 35 .…”
Section: Resultsunclassified
“…Our research results show that the usage rate of e-cigarettes among college students in Hangzhou is 2.5%. A cross-sectional study from Guangzhou, China showed that the usage rate of electronic cigarettes among college students in Guangzhou is about 19.7% 22 . The usage rate of electronic cigarettes in Hangzhou is relatively low, which may be related to the small sample size in this study.…”
Section: Discussionmentioning
confidence: 99%